2019
DOI: 10.1101/535260
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stimulation of the vagus nerve reduces learning in a go/no-go reinforcement learning task

Abstract: AbstractWhen facing decisions to approach rewards or to avoid punishments, we often figuratively go with our gut, and the impact of metabolic states such as hunger on motivation are well documented. However, whether and how vagal feedback signals from the gut influence instrumental actions is unknown. Here, we investigated the effect of non-invasive transcutaneous vagus nerve stimulation (tVNS) vs. sham (randomized cross-over design) on approach and avoidance behavior using an … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 67 publications
2
10
0
Order By: Relevance
“…Moreover, similar therapeutic effects have been reported for taVNS compared to implanted cervical VNS (Fang et al, 2016;Liu et al, 2016;Tu et al, 2018;. In line with the hypothesized potential of VNS to alter motivational processes via dopamine signaling, we recently found that taVNS affects the learning rate in a go/no-go taVNS increases vigor Neuser et al 5 reinforcement learning task (Kühnel et al, 2019). Thus, non-invasive taVNS may provide a novel and effective means to study the endogenous regulation of motivation according to homeostatic needs.…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…Moreover, similar therapeutic effects have been reported for taVNS compared to implanted cervical VNS (Fang et al, 2016;Liu et al, 2016;Tu et al, 2018;. In line with the hypothesized potential of VNS to alter motivational processes via dopamine signaling, we recently found that taVNS affects the learning rate in a go/no-go taVNS increases vigor Neuser et al 5 reinforcement learning task (Kühnel et al, 2019). Thus, non-invasive taVNS may provide a novel and effective means to study the endogenous regulation of motivation according to homeostatic needs.…”
Section: Introductionsupporting
confidence: 82%
“…Furthermore, vagal afferents regulate learning and memory via hippocampal modulation in rats suggesting a role in reward seeking (Suarez et al, 2018). Likewise, we have observed that non-invasive VNS changes instrumental action learning in humans (Kühnel et al, 2019). Within the feeding circuit, the NTS serves as a hub relaying metabolic information to the mid-and forebrain (de Lartigue, 2016;Grill & Hayes, 2012) including to dopaminergic neurons in the substantia nigra Han et al, 2018).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…The electrode was placed at the left cymba conchae (taVNS) or was turned upside down and placed at the earlobe (sham). Prior to each measurement, the stimulus intensity was individually adjusted based on subjective pain thresholds using concurrent VAS ratings [3]. As recommended by the manufacturer, the intensity was increased from 0.1 mA in 0.1 mA increments until participants reported a "tingling" sensation (which was supposed to not be painful).…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…Next, we placed the taVNS device on the participants' left ear according to the randomization protocol. The individual stimulation intensity was adjusted based on subjective pain thresholds using concurrent VAS ratings (for details, see [20]). We then recorded at least 30 minutes of EGG and calorimetry during active stimulation before the participant was debriefed.…”
Section: Introductionmentioning
confidence: 99%